Predictive factors in the treatment of Pseudo-Acanthosis Nigricans by Fractional Carbon Dioxide Laser and Glycolic Acid Peel - Ahmed Fathy State; Shaymaa ElMongy ElMongyMohammed; Ghada Elsayed Mohamed (Sociedade Brasileira de Dermatologia (SBD), 2023)
Background: Acanthosis nigricans is a common dermatological disorder characterized by hyperpigmented and hyperkeratotic velvety skin lesions. It can be a manifestation of systemic disease. Objective: This study aims to evaluate the clinical and laboratory predictive factors in the treatment of pseudo-acanthosis nigricans. Patients and methods: This study included 20 patients with pseudo-acanthosis nigricans from the outpatient clinic. All cases were subjected to fractional CO2 laser on the right side of the neck and glycolic acid peel 70% on the left side of the neck. Each patient was followed up for three and half months. Results: There was an overall improvement in area index, severity, and texture in the neck of cases with pseudo-acanthosis nigricans treated with fractional CO2 laser or Glycolic acid peel. Conclusion: There was no statistical significance when comparing the effect of laser or peeling on different age groups and obese or overweight cases.